Estrogen-functionalized liposomes grafted with glutathione-responsive sheddable chotooligosaccharides for the therapy of osteosarcoma. (1st January 2018) - Yin, Xuelei; Feng, Shuaishuai; Chi, Yingying; Liu, Jinhu; Sun, Kaoxiang; Guo, Chuanyou; Wu, Zimei
Abstract: An estrogen (ES)-functionalized cationic liposomal system was developed and exploited for targeted delivery to osteosarcoma. Natural biocompatible chotooligosaccharides (COS, MW2-5 KDa) were covalently tethered to the liposomal surface through a disulfate bond (-SS-) to confer reduction-responsive COS detachment, whereas estrogen was grafted via polyethylene glycol (PEG 2 K) chain to achieve estrogen receptor-targeting. The liposomal carriers were prepared by the ethanol injection method and fluorescent anticancer drug doxorubicin (DOX) was loaded with ammonium sulfate gradient. The physicochemical properties, reduction-sensitivity, and the roles of estrogen on cellular uptake and tumor-targeting were studied. The Chol-SS-COS/ES/DOX liposomes were spherical with an average size about 110 nm, and high encapsulation efficiency. The liposomes were stable in physiological condition but rapidly release the payload in response to tumoral intracellular glutathione (20 mM). MTT cytotoxicity assay confirmed that Chol-SS-COS/ES/DOX liposomes exhibited higher cytotoxicity to MG63 osteosarcoma cells than to liver cells (LO2). Flow cytometry (FCM) and confocal laser scanning microscopy revealed that cellular uptake of Chol-SS-COS/ES/DOX liposomes by MG63, than the free DOX or Chol-SS-COS/DOX. Ex vivo fluorescence distribution study showed that the multifunctional liposomes selectively accumulated in the MG63 xenografts versus the organs. Chol-SS-COS/ES/DOX liposomes strongly inhibited the tumor growth and enhanced the animal survival rate. Overall, the COS grafted estrogen-functionalized cationic liposomes, fortified with glutathione-responsiveness, showed great potential for specific intracellular drug delivery to estrogen receptor-expressing tumors such as osteosarcoma.